Legislation and public policies for children and adolescents in Costa Rica during the years 1989 to 2019 - Barrantes Pereira, Rolando (2023)
This article presents the results of a literature review and analysis study that delves into the legislation and public policy of children and adolescents in Costa Rica between the years 1989, the date of the Convention on the Rights of the Child, and 2019. This follow-up to the legislation on the rights of children and adolescents and its respective analysis based on specific criteria, seeks to build inputs, indicators, and references to develop subsequent recommendations from the Inter-university Thematic Observatory for the rights of children and adolescents (OBINA) that can serve as inputs for decision-making in this matter and to generate a baseline for further research. This investigation is located within the framework of action of the OBINA and the Liaison and Public Policy sub-committee; thus, responding to its objectives defined from the strategic and operational plan of the Observatory. In order to carry out this research exercise, three phases are proposed that entail the identification of laws and policies, the elaboration and definition of criteria for analysis and the respective study by decade, covering the period of approximately 30 years. The main results show the country's interest in generating regulations and policies for the promotion and defense of children's and adolescents' rights. The results also demonstrate how there is still a debt in this matter and a lack of even greater positioning in the framework of public policy, so that it is a transcendental issue and a transversal axis present in all the country's political work.